The determinants of international flows of US currency - Rebecca Hellerstein; William Ryan (Federal Reserve Bank of New York, 2009)
This paper examines the determinants of cross-border flows of U.S. dollar banknotes, using a new panel data set of bilateral flows between the United States and 103 countries from 1990 to 2007. We show that a gravity model explains international flows of currency as well as it explains international flows of goods and financial assets. We find important roles for market size and transaction costs, consistent with the traditional gravity framework, as well as roles for financial depth, the behavior of the nominal exchange rate, the size of the informal sector, the amount of remittance credits, the degree of competition with the euro, and the history of macroeconomic instability over the previous generation. We find no role for official trade flows of goods. Our results thus confirm several hypotheses about the determinants of using a secondary currency.
Keywords: F24; F3; F31; F4; O17; 330; Currency substitution; secondary currency; gravity model; U.S. dollar